Mental health of general practitioners and family medicine specialists 2 years into the COVID-19 pandemic - Marija Zafirovska; Marija Zafirovska; Jelena Danilenko; Jelena Danilenko; Aleksandar Zafirovski; Aleksandar Zafirovski; Aleksandar Zafirovski; Kristien Coteur; Heidrun Lingner; Cristián Andrés Frigolett; Milena Cojić; Mustafa Kürşat Şahin; et al. (Frontiers in Public Health)
IntroductionThe COVID-19 pandemic has significantly impacted general medical practice by altering work structures and increasing teamwork while also adversely affecting the mental health of general practitioners and family medicine specialists. This study assesses depression, anxiety, and fear levels among general practitioners and family medicine specialists in Europe 2 years after the COVID-19 pandemic’s onset, and it explores influencing factors.MethodsThis observational cross-sectional study included participants from 13 European countries. Data was collected from May to August 2022 with an anonymous online survey incorporating validated questionnaires for depression (PHQ-9), anxiety (GAD-7), and fear of COVID-19 (FCV-19S). Data analysis involved descriptive statistics, correlation tests, and linear regression.ResultsA total of 1,723 participants completed the survey. Findings indicated an overall mild to moderate levels of anxiety (GAD-7: 5.4 ± 4.76) and depression (PHQ-9: 6.33 ± 5.43), and moderate fear of COVID-19 (FCV-19: 12.84 ± 5.29). Key determinants of anxiety, fear, and depression included country, at-risk status, patient non-compliance, and mental health history. Sex influenced anxiety and fear, losing co-workers to COVID-19 influenced anxiety and depression, while losing relatives or friends influenced fear.ConclusionTwo years into the pandemic, European general practitioners and family medicine specialists showed mild to moderate levels of anxiety, depression, and fear. Country, at-risk status, mental health history, and work-related challenges significantly affected mental health. Crucial interventions are needed to support healthcare workers during pandemics, focusing on protective measures, stable work environments, and coping strategies for anxiety and depression.